RETRACTED (ditarik) : Penerapan Data Market Query (DMQ) Pada Sistem Penilaian Berbasis Yii Framework - Qurotul Aini; Untung Rahardja; Ayu Martha Wardani (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2018)
RETRACTED (ditarik) Following a rigorous, carefully concerns and communication between the publisher and the authors of the article published in Positif : Jurnal Sistem dan Teknologi Informasi to article entitled â€œPenerapan Data Market Query (DMQ) pada Sistem Penilaian Berbasis Yii Frameworkâ€ Vol 4, No 2, pp. 95-102, November 2018. This paper has been withdrawn at the request of the author and has been retracted. This article has been retracted by the publisher because it was published twice in error ( InfoTekJar: Jurnal Nasional Informatika dan Teknologi Jaringan, 3(1), pp.26-31.) during a change in production systems. The publisher apologizes to the authors and readers for the error and any inconvenience caused.